2011
DOI: 10.1017/s0031182011001120
|View full text |Cite
|
Sign up to set email alerts
|

Increased metacyclogenesis of antimony-resistant Leishmania donovani clinical lines

Abstract: Mathematical models predict that the future of epidemics of drug-resistant pathogens depends in part on the competitive fitness of drug-resistant strains. Considering metacyclogenesis (differentiation process essential for infectivity) as a major contributor to the fitness of Leishmania donovani, we tested its relationship with pentavalent antimony (SbV) resistance in clinical lines. Different methods for the assessment of metacyclogenesis were cross-validated: gene expression profiling (META1 and SHERP), morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…By Ficoll enrichment and qRT-PCR experiments, we were able to determine that the metacyclogenesis event takes place in the resistant parasites to a lesser extent than in WT cells. Conversely, a previous report associated increased metacyclogenesis with antimonial resistance in L. donovani (60), and our own results in L. major populations resistant to HePC have led us to link reduced HePC susceptibility to augmented metacyclogenesis rates (61). Altogether, these results strongly suggest that the specific genetic background of the parasite has a key role in determining the parasite response to resistance emergence, not only among species, but also among species-specific strains.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…By Ficoll enrichment and qRT-PCR experiments, we were able to determine that the metacyclogenesis event takes place in the resistant parasites to a lesser extent than in WT cells. Conversely, a previous report associated increased metacyclogenesis with antimonial resistance in L. donovani (60), and our own results in L. major populations resistant to HePC have led us to link reduced HePC susceptibility to augmented metacyclogenesis rates (61). Altogether, these results strongly suggest that the specific genetic background of the parasite has a key role in determining the parasite response to resistance emergence, not only among species, but also among species-specific strains.…”
Section: Discussionsupporting
confidence: 47%
“…In fact, the higher metacyclogenesis levels in clinical isolates of L. donovani resistant to antimony have been shown to correlate with greater success of in vitro infection (60). Additionally, it is worth noting that differences in phenotypic outcome are possible when drug selection, e.g., paromomycin, is performed in axenic promastigotes or intracellular amastigotes (19,62).…”
Section: Discussionmentioning
confidence: 99%
“…Promastigotes (10 6 cells/ml in M199 medium with 20% FBS) were added to 96-well plates containing serial dilutions of freshly isolated human serum (0.78 to 50%), and the plates were incubated at 37°C for 60 min. Plates were incubated at 25°C for 24 h after the addition of 40 l of cold EDTA and 24 l of resazurin, and then fluorescence was measured using a fluorometer (Tecan) (24).…”
Section: Culture Of Parasitesmentioning
confidence: 99%
“…Thus it is not hard to believe that it can develop drug resistance without paying a fitness cost in return. In a study relating metacyclogenesis (parameter for infectivity) to antimony resistance in L. donovani it was established that capacity of differentiation was significantly higher in antimony-resistant cells [10]. Another report about clinical isolates taken from Nepalese strains of L. donovani showed that resistant cells had the ability to attain a higher parasite density, contained a higher number of metacyclics, and possessed increased capacity of in vivo infection than sensitive cells.…”
Section: Virulence and Drug Resistance: Are They Related?mentioning
confidence: 99%